On hamiltonicity of 1-tough triangle-free graphs - Wei Zheng; Hajo Broersma; Ligong Wang (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2021)
Let ω(G) denote the number of components of a graph G. A connected graph G is said to be 1-tough if ω(G − X)≤|X| for all X ⊆ V(G) with ω(G − X)>1. It is well-known that every hamiltonian graph is 1-tough, but that the reverse statement is not true in general, and even not for triangle-free graphs. We present two classes of triangle-free graphs for which the reverse statement holds, i.e., for which hamiltonicity and 1-toughness are equivalent. Our two main results give partial answers to two conjectures due to Nikoghosyan.